الأعراض والعلامات الكاشفة لداء السكري - مرعي, منيف; درويش, علي; الجندي, سلاف (Latakia University Journal -Medical Sciences Series, 2019)
تهدف الدراسة إلى تحديد أكثر الأعراض والعلامات الكاشفة لداء السكري في مدينة اللاذقية وريفها. وقد شملت هذه الدراسة 300 مريضا ومريضة مصابين بالداء السكري من مراجعي العيادة الداخلية وقسم الداخلية بمشفى الأسد الجامعي وانحصرت ضمن مرضى السكري النمط . II من خلال الدراسة تبين أن العرض الكاشف الأكثر تواترا لمرضى السكري في مدينة اللاذقية وريفها هو البوال والسهاف يليه تحليل السكر المجرى من قبل المريض نفسه أو من طبي أجرى له تحاليل عامة وترتفع هذه النسبة في حال وجود قصة عائلية لدى المريض كما لوحظ ارتفاع نسبة الكشف من خلال الاختلاطات عند الذين ليس لديهم قصة عائلية . وتبين الدراسة أيضاً أن الإنتانات البولية التناسلية المتكررة كعرض كاشف لداء السكري تزداد عند الإناث نسبة للذكور الذين تزداد عندهم نسبة الكشف عبر إنتانات الفم واللثة والاختلاطات القلبية . This study aims to determine most of the signs and symptoms which reveal Diabetes Mellitus (DM) in Lattakia City and its countryside. We have studied 300 outpatients with DM admitted to the internal clinic and department at Al-Assad University Hospital. This study is restricted to DM type Π.We have found that the most frequent revealing symptoms of Diabetes Mellitus in Lattakia City and its countryside are polyuria and polydipsia; this is followed by the patient himself having blood glucose analyses done or by the doctor doing general analyses for him; this rate increases with those with a family history. We have also noticed that the rate of revealing by complications increases in patients without a family history. We have found that the rate of revealing by the recurrent genitourinary track infections is raised in females compared to males who have a higher rate of revealing through gum infections and cardiovascular complications.